Basketball - Harley, R.; Mills, S.; Bliss, A. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
The design of any individual physical training Programme will depend upon a variety of factors including (but are not exclusive to) training status of the player, time and facilities available, the player's physical strengths and weaknesses, and the volume/intensity of training stimulus being implemented through on court sports specific training. Using the assessments and screening tools described in the chapter, coaches can prioritise the areas in which players require improvement as part of their individual training programmes and monitor the effectiveness of their interventions. Strength and conditioning coaches working in basketball are encouraged to develop a philosophy of practice based upon the evidence provided and develop individual training programmes for their clients aimed at consolidating their strengths and addressing areas of weakness. Effective physical conditioning for basketball players is multifaceted and complex. From an energy systems perspective, basketball athletes are required to effectively develop both - aerobic and anaerobic energy pathways to meet the demands of match play. From a muscular - strength perspective, developing strong, robust players who express sound movement capabilities is desirable. Improving muscular strength (throughout the strength/ speed continuum) can bring about desirable alterations to the physical qualities of the basketball player and helps to reduce the risk of lower limb injuries that were highlighted earlier in the chapter. The foundation of any strength programme is to develop the physical competency of the player by addressing any muscle imbalances, improving functional range of motion and improving sports specific movement force production. These improvements can help to influence in-game movements (jumping, landing, change of direction, etc.) and therefore the likelihood of successful performance and reduction in injury prevalence. Finally the aims of the strength and conditioning coach should be integrated with the aims of other members of the athlete support team (e.g. technical coaches, team managers, etc.) to help create a successful, well designed, and considered strength and conditioning support programme which needs to be communicated effectively to the athletes to aid compliance.